Imidazolium Based Fluorous N‐Heterocyclic Carbenes as Effective and Recyclable Organocatalysts for Redox Esterification. Issue 24 (9th June 2020) - Červenková Šťastná, Lucie; Bílková, Veronika; Cézová, Tereza; Cuřínová, Petra; Karban, Jindřich; Čermák, Jan; Krupková, Alena; Strašák, Tomáš
Abstract : A series of new highly fluorophilic ionic liquids ( f > 110) was synthetized from 3‐iodopropyltris(3, 3, 4, 4, 5, 5, 6, 6, 7, 7, 8, 8, 8‐tridecafluorooctyl)silane and N‐alkyl imidazoles, followed by anion exchange. N‐heterocyclic carbenes generated in situ from obtained imidazolium salts were employed to catalyze redox esterification ( umpolung ) of cinnamaldehyde with alcohols. The most effective N ‐methyl derivative with iodide as a counter anion was studied in detail with respect to the optimization of reaction conditions, substrate scope and recyclability. Recovery of the precatalyst was achieved using either fluorous extraction or performing the reaction in suitable fluorous biphase system with direct recycling of the fluorinated precatalyst phase. For both tested options, the catalytic activity did not significantly decrease within 5 subsequent cycles. The redox esterification was shown to proceed also in supercritical carbon dioxide (scCO2 ) as an alternative solvent where the activity of the fluorinated catalyst was also superior to the nonfluorinated model, while retaining the benefit of easy recycling. Abstract : Let's get fluorophilic! Tagging the imidazolium ionic liquids catalytically active in redox esterification with large fluorous substituents enables their facile recovery from reaction mixtures and multiple reuse without loss of activity. It also enables their application as catalysts in fluorous biphase catalysis and supercritical CO2 .